Competitiveness and Factors Affecting Indonesian Food Industry’s Export to Regional Comprehensive Economic Partnership - Mia Ayu Wardani; Sri Mulatsih; Wiwiek Rindayati (ETIKONOMI, 2018)
Regional Comprehensive Economic Partnership (RCEP) is regional cooperation between ASEAN, Australia, China, India, Japan, South Korea and New Zealand. The vast potential of the RCEP provides an opportunity for the improvement of the Indonesian economy. This study aims to analyze the comparative advantages and dynamics export of Indonesia’s food industry as well as the factors affecting exports. The methods used Revealed Comparative Advantage (RCA), Export Product Dynamic (EPD), and panel data. The results indicate that food industry generally has strong competitiveness in the RCEP market except in Australia, Cambodia, Japan, Korea and Laos. Meanwhile, the dynamics position of food industry exports is rising star in ten countries, and the rest are in the position of falling star and retreat. Factors that influence food exports are economic distance, real GDP per capita of the destination country, the population of the destination country, price export, trade openness and tariff.DOI: 10.15408/etk.v17i2.7239